A concept for a smart web portal development in intelligence information system based on SOA - Ackoski, Jugoslav; Trajkovik, Vladimir; Serafimova, Nevena (My University, 2013)
This paper presents a concept for Service Oriented Architecture (SOA) approach in a prototype of an Intelligence Information System (IIS). IIS prototype, based on SOA, could offer better coordination among institutions involved in intelligence thus providing increase of intelligence effectiveness. This approach can serve as a foundation for the establishment of the Integrated Intelligence System, which is based on services as software components. Here, our main interest is the upgrading of the Intelligence Information System with a Smart Web Portal, composed of three modules combined together to automate the Intelligence Cycle. The purpose of this feature is to serve as a platform for integrating Intelligence’s information collected by different sources and ensure information delivery to the right end-user.